2022
DOI: 10.23960/jsl.v10i3.594
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Mechanical Properties of Bamboo Oriented Strand Board Under Various Post-Thermal Treatment Duration

Abstract: Post-treatment of bamboo-oriented strand board (BOSB) through thermal modification can be an alternative to improve BOSB quality. This study aimed to analyze the effect of post-thermal treatment duration on the physical and mechanical properties of BOSB. Three-layers BOSB with a target density of 0.7 g/cm3 was made with the core layer perpendicular to the surface and bonded with 8% phenol-formaldehyde resin. The BOSB produced was then thermally-modified at 160°C for 1, 2, and 3 h. The physical and mechanical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Previous research showed that BOSB glued with MDI adhesive and manufactured by D. asper strand with SR values of 76.6 and 73.8 had good mechanical and physical properties (Febrianto et al, 2009) . Our previous studies showed that BOSB bonded with PF adhesive exhibited good physical and mechanical properties when AR values were greater than three and SR greater than 100 (Mangurai et al, 2022;Maulana, 2016;Maulana et al, 2017;Maulana et al, 2019;Maulana et al, 2021c).…”
Section: Strand Geometrymentioning
confidence: 97%
See 1 more Smart Citation
“…Previous research showed that BOSB glued with MDI adhesive and manufactured by D. asper strand with SR values of 76.6 and 73.8 had good mechanical and physical properties (Febrianto et al, 2009) . Our previous studies showed that BOSB bonded with PF adhesive exhibited good physical and mechanical properties when AR values were greater than three and SR greater than 100 (Mangurai et al, 2022;Maulana, 2016;Maulana et al, 2017;Maulana et al, 2019;Maulana et al, 2021c).…”
Section: Strand Geometrymentioning
confidence: 97%
“…Extractives disrupted the adhesion process during the manufacturing of BOSB, resulting in OSB of inferior grade. According to earlier investigations, extractive materials might be removed from bamboo strands by heating them (Fatrawana et al, 2019;Maulana et al, 2021b;Maulana, 2016;Maulana et al, 2017;Maulana et al, 2019;Maulana et al, 2020;Maulana et al, 2021a), improved dimensional stability and mechanical characteristics of BOSB (Mangurai et al, 2022) . However, high energy consumption in the heat treatment process still needs to be considered.…”
Section: Introductionmentioning
confidence: 99%
“…Several species of bamboo such as andong (Gigantochloa verticillata), ampel (Bambusa vulgaris), and betung (Dendrocalamus asper), have been investigated for their feasibility for developing BOSB. Among these, betung bamboo has evident to show satisfied physical, mechanical, and wettability properties, and it is compatible for BOSB production (Baiti et al 2021b;Febrianto et al 2012Febrianto et al , 2015Mangurai et al 2022;Maulana et al 2019;Murda et al 2022a).…”
Section: Introductionmentioning
confidence: 99%
“…The type of adhesive and its content were basic factors that influenced the quality of biocomposite products that affect physical and mechanical properties (Febrianto et al 2015;Hariz et al 2021). In the previous studies, the manufacturing process of BOSB used the formaldehyde adhesive base (Mangurai et al 2022;Maulana et al 2019), which may cause harmful environmental formaldehyde emissions. To avoid this issue, this research uses a formaldehydefree adhesive, especially methylene diphenyl diisocyanate (MDI), to produce BOSB.…”
Section: Introductionmentioning
confidence: 99%